Assessment of day spa premises spatial organization, components and services towards Muslim friendly elements - Othman, Rashidi; Mohd Noor, Nur Fadhlina; Mohd Din, Shamzani Affendy; Ahmad, Nurliyana; Hashim, Khairusy Syakirin Has-Yun; Mahamod, Lukman Hakim (2019)
The paper aims to study spa design, social interaction and services that merged the modern spa with an Islamic point of view. The selected day spas are Lanna Thai Spa and Ayur-V Spa. The method used is structured observation through inventory and analysis, on-site measurement and in-depth Interviews with an expert. The findings established that both day spa spaces are is not segregated by gender which means no specific area for male or female clients to do their treatments and therapists are not served their clients based on gender. Both spas also offered services that contradicted Islamic principles. To fulfill the crucial gap of this knowledge, the formation of a Muslim friendly spa is recommended to serve the Muslims clients in preserving their awrah and privacy.